Ursula virgo et turba virginum w poezji Hildegardy z Bingen - Miazek-Męczyńska, Monika (My University, 2013)
The lyric poetry of Hildegard of Bingen still waits for a more detailed elaboration in Polish. This article pretends only to present a few poems – songs from a Symphonia harmonicae caelestiarum revelationum, it means 13 poems connected with a history of saint Ursula, virgin and martyr, who was killed by Huns in Cologne with eleven thousand holy virgins (according tradition). Their martyrdom described in a poetical vision by Hildegard (poems 43-55 in edition P. Barth, M.-I. Ritscher, J. Schmidt-Görg, Hildegard von Bingen: Lieder, Salzburg 1992) encouraged the auditors of songs (especially the nuns from Rupertsberg) to deliver up their virginity to God. This cycle of songs as a commendation of a mystical marriage and relationship of Christ and the Church could be interpreted in a context of the Old Testament (for example the Song of Songs) and patriarchal texts, like Symposium of saint Dionis of Olimp. In Hildegrad’s poetry saint Ursula accomplished the God’s plane of salvation as a successor of Eve and Maria and as exemple for all women tending the Eternal Life.
Keywords: Huldagarda z Bingen; poezja średniowieczna; święta Urszula; virgo